Late Barremian–early Aptian ammonite bioevents from the Urgonian-type series of Provence, southeast France: Regional stratigraphic correlations and implications for dating the peri-Vocontian carbonate platforms. (October 2018) - Frau, Camille; Tendil, Anthony J.-B.; Lanteaume, Cyprien; Masse, Jean-Pierre; Pictet, Antoine; Bulot, Luc G.; Luber, Tim L.; Redfern, Jonathan; Borgomano, Jean R.; Léonide, Philippe; Fournier, François; Massonnat, Gérard
Abstract: This work provides a new ammonite age-calibration of the rudistid limestones of the Urgonian-type Provence carbonate platform (Southeast France) based on sampling along three ∼200 km-long platform-to-basin transects and re-examination of historical collections. Ammonite key findings indicate that the first rudistid platform stage (including the Agriopleura and requieniid–monopleurid beds) develops and spreads northward through the Toxancyloceras vandenheckii – Gerhardtia sartousiana zones interval (lower upper Barremian). This stage is interrupted by the tectonically-induced deepening of the southern Provence domain during the Imerites giraudi Zone while the northern regions records the massive deposition of Palorbitolina – Heteraster beds. Recovery of the rudistid carbonate system is illustrated by the development of caprinid-bearing rudistid limestones in the North Provence domain through the Martelites sarasini Subzone (lower Martelites sarasini Zone, uppermost Barremian), which shows a bidirectional progradation toward the South Provence and Vocontian basins. The caprinid-bearing limestones terminate at a short-term exposure and are overlain by cherty–oobioclastic deposits spanning the Pseudocrioceras waagenoides Subzone (upper M. sarasini Zone) to the lower Deshayesites forbesi Zone. A regional-wide flooding of the study area is illustrated by the abrupt change to a marl-dominated regime occurring in the upper D. forbesi Zone. Compared to the previous datings, the Barremian/Aptian boundary should be relocated in the lower part of the post-caprinid, cherty–oobioclastic deposits although its precise level cannot be fixed due to the lack of a continuous ammonite record. Ammonite age-calibration of the surrounding Urgonian rudistid platform series is discussed and gives evidence of a comparable twofold demise of the peri-Vocontian rudistid biota during the uppermost Barremian. Accordingly, the link between the final demise of the peri-Vocontian rudistid biota and the onset and/or culmination of the mid-early Aptian Oceanic Anoxic Event (OAE) 1a should be reconsidered.